(untitled) (Research, Society and Development, 2025)
This study aims to present an analysis of the use of low-cost didactic materials as support tools for practical teaching in Production Management and Production Engineering programs, considering their contribution to the effectiveness of active methodologies and experience-based learning. In a constantly evolving educational landscape, and given the need to align technical training with contemporary demands of the productive sector, the study discusses accessible alternatives that enhance student engagement, content retention, and the development of relevant technical and socio-emotional competencies. The methodological approach involved a literature review conducted in the Scopus and Capes databases, complemented by a basic bibliometric analysis aimed at understanding the scientific landscape on the subject. The results indicate a growing academic interest in pedagogical approaches that integrate theory and practice through accessible and easily implementable resources. The study concludes that low-cost didactic kits constitute viable tools for promoting more contextualized, inclusive, and effective learning, especially in public institutions that face budget constraints.